Teaching and learning with geotechnologies on primary education: Students’ perceptions - Ribeiro, Vítor (2018)
Recent developments in computer and internet technology have resulted in many education reforms. Classrooms have been equipped to allow technological advances. Yet these rapid technological developments have not been accompanied by teachers’ education. The migration of teachers’ traditional resources to “digital” students is not always achieved. In this context, Geographic Information Systems (GIS) is powerful technology to enhance the teaching and learning of several subjects, promotion of interdisciplinary approaches, and combination of research and online maps to motivate students to learn. In this article, Portugal’s territory GIS education context is analysed along with an experience with primary students.Primary education; Geotechnologies; GIS; Teaching and learning; Spatial thinking.